(untitled) (Detroit, 2006)
Primary sources give students and researchers a glimpse into important events by providing the words and images of the original participants. This new volume in Gale's Social Issues Primary Sources Collection focuses on medicine, health, and bioethics from the nineteenth, twentieth, and twenty-first centuries. An international group of scholars provided commentary to help place the chosen primary sources in context. The interdisciplinary approach demonstrates the links between the medical and the social sciences,...
Keywords: Medical ethics,Bioethics,Medicine,Đạo đức y học; History,History,History,Lịch sử